Role of nutraceutical against exposure to pesticide residues: power of bioactive compounds - Sajad, Mabil; Shabir, Shabnam; Singh, Sandeep Kumar; Bhardwaj, Rima; Alsanie, Walaa F.; Alamri, Abdulhakeem S.; Alhomrani, Majid; Alsharif, Abdulaziz; Vamanu, Emanuel; Singh, Mahendra P. (Frontiers in Nutrition, 2024)
Pesticides play a crucial role in modern agriculture, aiding in the protection of crops from pests and diseases. However, their indiscriminate use has raised concerns about their potential adverse effects on human health and the environment. Pesticide residues in food and water supplies are a serious health hazards to the general public since long-term exposure can cause cancer, endocrine disruption, and neurotoxicity, among other health problems. In response to these concerns, researchers and health professionals have been exploring alternative approaches to mitigate the toxic effects of pesticide residues. Bioactive substances called nutraceuticals that come from whole foods including fruits, vegetables, herbs, and spices have drawn interest because of their ability to mitigate the negative effects of pesticide residues. These substances, which include minerals, vitamins, antioxidants, and polyphenols, have a variety of biological actions that may assist in the body's detoxification and healing of harm from pesticide exposure. In this context, this review aims to explore the potential of nutraceutical interventions as a promising strategy to mitigate the toxic effects of pesticide residues.